Avaliação histomorfométrica do corioalantóide na espécie equina com o uso da análise digital de imagens. - Castro da Silva, Gabriela; Wayne Nogueira, Carlos Eduardo; Dahl Corcini, Carine; Sérgio Varela Júnior, Antônio; da Rosa Curcio, Bruna (Scire Salutis)
Fetal health and growth are directly influenced by placental development and function. Digital image analysis based on tissue samples shows promise both for reducing the subjectivity of traditional evaluations and for reducing the time needed to analyze each sample. The aim of this study is to describe the steps involved in assessing the placenta at term in mares, with an emphasis on evaluating micro-cotyledon histomorphometry using digital image analysis. Twelve placentas from Criollo mares were collected immediately after elimination in the immediate postpartum period. After macroscopic evaluation, samples were taken from the regions corresponding to the gravid horn, non-gravid horn and uterine body. Digitized images were taken of the segments using a high-resolution camera attached to the microscope and then processed using NIH ImageJ software. Twelve Criollo mares were followed up, with an average age of 8.4 ± 4 years, with eutocic foaling of a single healthy foal. The placentas were eliminated in 25.3 ± 10 minutes and weighed 4.5 ± 0.7 kg. Histological evaluation revealed findings characteristic of healthy placentas at term in horses. In the digital evaluation, the images were evaluated in RGB color with the total number of pixels calibrated to μm. Quantification of the microcotyledon and capillary area was carried out using the Color Threshold macro, with the color range adjusted using the RGB scale. A total of 360 photos from the 3 placental areas of the 12 mares were evaluated (30 photos per mare). The histomorphometric measurements obtained showed a normal distribution pattern and the homogeneity of the data can be seen in the low dispersion values between the mares evaluated. It can be concluded that the use of digital image analysis to evaluate the microcotyledon histomorphometry of equine placentas at term proved to be an adequate tool for obtaining objective information on this structure.